Knowledge of lateralized brain function can contribute to animal welfare - Rogers, Lesley J. (Frontiers in Veterinary Science, 2023)
The specialized functions of each hemisphere of the vertebrate brain are summarised together with the current evidence of lateralized behaviour in farm and companion animals, as shown by the eye or ear used to attend and respond to stimuli. Forelimb preference is another manifestation of hemispheric lateralization, as shown by differences in behaviour between left- and right-handed primates, left- and right-pawed dogs and cats and left- and right-limb preferring horses. Left-limb preference reflects right hemisphere use and is associated with negative cognitive bias. Positive cognitive bias is associated with right-limb and left-hemisphere preference. Strength of lateralization is also associated with behaviour. Animals with weak lateralization of the brain are unable to attend to more than one task at a time and they are more easily stressed than animals with strong lateralization. This difference is found also in domesticated species with strong versus weak limb preferences. Individuals with left-limb or ambilateral preference have a bias to express functions of the right hemisphere, heightened fear and aggression and greater susceptibility to stress. Recognition of lateralized behaviour can lead to improved welfare by detecting those animals most likely to suffer fear and distress and by indicating housing conditions and handling procedures that cause stress.